MODEL PENDUGA JUMLAH PRODUKSI PIL KB TRINORDIOL*-28: STUDI KASUS PT.SUNTHI SEPURI - Bay Haqi (LPPM, 2011)
The problems that often arise in this world of uncertainty, fuzzy logic is a method for analyzing systems that contain uncertainty. In this study mamdani or requently used method is also known by the method of Min - Max. The design of the system to get the output is done in stages - stage (a) formation of fuzzy set, (b) Application implication function, (c) establish the rules - the rules, (d) the assertion (defuzzyfication). In this study defuzzyfication performed using centroid method. In this method the value defuzzyfikasi move subtly, so that changes to the fuzzy set will also move with the smooth. From the research that has been done, by entering the input variable number of requests and the amount of inventory for the predictable amount of production that must be done. Key Words: Uncertainty, Total production, fuzzy logic.